Plugged in. (American City & County, 2007)
This section offers news related to local government procurement in the U.S. A case management software from Lagan was purchased by the Tennessee Department of Human Services. The Sheriff's Office of Columbia County, Georgia has acquired computer-aided dispatch, records management, jail management, mobile computing and field reporting computer software from SunGard. A field survey system was acquired by the West Virginia Division of Forestry from GeoAge.